Population Structure of mtDNA Variation due to Pleistocene Fluctuations in the South American Maned Wolf (Chrysocyon brachyurus, Illiger, 1815): Management Units for Conservation - Gonzalez, Susana; Cosse, Mariana; del Rosario Franco, Maria; Emmons, Louise; Vynne, Carly; Barbanti Duarte, Jose Mauricio [UNESP]; Beccacesi, Marcelo D.; Maldonado, Jesus E. (Oxford Univ Press Inc, 2015)
The maned wolf (Chrysocyon brachyurus) is one of the largest South American canids, and conservation across this charismatic carnivore's large range is presently hampered by a lack of knowledge about possible natural subdivisions which could influence the population's viability. To elucidate the phylogeographic patterns and demographic history of the species, we used 2 mtDNA markers (D-loop and cytochrome b) from 87 individuals collected throughout their range, in Argentina, Bolivia, Brazil, and Uruguay. We found moderate levels of haplotype and nucleotide diversity, and the 14 D-loop haplotypes were closely related. Genetic structure results revealed 4 groups, and when coupled with model inferences from a coalescent analysis, suggested that maned wolves have undergone demographic fluctuations due to changes in climate and habitat during the Pleistocene glaciation period approximately 24 000 years before present (YBP). This genetic signature points to an event that occurred within the timing estimated for the start of the contraction of the Cerrado around 50 000 YBP. Our results reveal a genetic signature of population size expansion followed by contraction during Pleistocene interglaciations, which had similar impacts on other South American mammals. The 4 groups should for now be considered management units, within which future monitoring efforts should be conducted independently.
Keywords: climate change; conservation genetic units; gene flow; landscape fragmentation; maned wolf